BOTTOM-UP CONSTRUCTION IN SANUR TOURISM AREA: LINGUISTIC LANDSCAPE APPROACH - I Made Teja Kumara Sena; Luh Putu Laksminy (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Abstract: his study aims to describe the construction of a bottom-up sign in the linguistic landscape of the Sanur tourism area. The data were collected using observation, and interview methods along with (Landry and Bourhis (1997) and Ben-Rafael et al. (2006) theories to analyze the study. theories to analyze the study. The result showed that a total of 419 bottom-up signs were found in the Sanur tourism area, and English as the dominant language appear inside the bottom-up sign. The construction of bottom-up signs by individuals specifically the use of the English language inside the bottom-up signs has a similar purpose that is English as a medium of language for marketing tools for these individuals.